1953
DOI: 10.1099/00221287-8-3-464
|View full text |Cite
|
Sign up to set email alerts
|

The Cultivation of Actinomyces israelii in a Progressively Less Complex Medium

Abstract: SUMMARY: Six strains of Actinomyces israelii were trained to grow in continued subculture on a medium composed of 99 volumes of 1 yo casein hydrolysate + 1 volume of heart broth, the mixture containing 0.5 yo (w/v) glucose. Poor growth of limited viability was obtained in a medium consisting of 1 yo casein hydrolysate + 0.5 Yo glucose (w/v) only. The addition of a wide variety of different amino-acids, fatty acids, growth factors and mineral salts to certain of the less complex media did not compensate for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1956
1956
1966
1966

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Erikson & Porteous (1953) found that on a heart broth casein digest medium, Actinomyces strains produced lactic acid equivalent to only 30-60 yo of the glucose utilized; other products were not reported.…”
Section: Comparison Of Actinomyces Spp With L Bifidus 443mentioning
confidence: 99%
“…Erikson & Porteous (1953) found that on a heart broth casein digest medium, Actinomyces strains produced lactic acid equivalent to only 30-60 yo of the glucose utilized; other products were not reported.…”
Section: Comparison Of Actinomyces Spp With L Bifidus 443mentioning
confidence: 99%
“…israelii (Erikson & Porteous, 1953). Thus the fact that neither coenzyme A (Christie & Porteous, 1962) nor pantothenic acid was required for growth was surprising for a reputedly fastidious anaerobic heterotroph.…”
Section: Discussionmentioning
confidence: 99%
“…Every precaution was taken in the present work to avoid contamination (Christie & Porteous, 1962) and no evidence of contamination of experimental cultures was found; Erikson & Porteous (1955) have, however, emphasized the difficulties of detecting small numbers of contaminants within the mycelial colonies of A . israelii and pointed out that changes in the colony form in liquid or on surface media may not be apparent in relatively lightly contaminated cultures of A .…”
mentioning
confidence: 99%
“…Cultures were maintained as described by Erikson & Porteous (1953). (1953) were used in the first and second stages of the technique to be described.…”
Section: Organismsmentioning
confidence: 99%
“…diameter; the supernatant medium remains clear at all stages of growth. The colonies, variously described as ' cauliflower ' or ' bread-crumb ' in appearance (Erikson, 1940; Erikson & Porteous, 1953), do not disperse on mild agitation of the culture vessel although the colonies of certain contaminated cultures will disintegrate (Erikson & Porteous, 1955). The colonies of different pure strains in liquid culture vary in consistency, from those which can be fragmented into smaller colonies by the tip of a Pasteur pipette to those which are so tough as virtually to resist fragmentation by this means.…”
Section: Introductionmentioning
confidence: 99%